Model Sistem Dinamik Pengelolaan Sampah Dengan Fasilitas TPS 3R di Kelurahan Benda Baru Kota Tangerang Selatan - Yustiati, Yustiati; Sodikin, Sodikin; Aji, Sandra Sukmaning (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
The objectives of the study were a) To analyze the amount of household waste generated in Benda Baru Village and community behavior in managing household waste; b) To analyze the effectiveness of waste banks and TPS 3R in Benda Baru Village; c) To prepare recommendations for community-based waste management policy scenarios, TPS3R in Benda Baru Village. The method used to analyze waste management in Benda Baru Village with TPS 3R facilities is to use a simulation model with a dynamic system approach. Dynamic model simulations were carried out for 3 policy scenarios, namely (1) Business as Usual (BAU) scenario for existing waste management processes can reduce waste generation by 25%; (2) moderate scenario with the addition of TPS 3R units can reduce waste generation by 43%; (3) optimistic scenario by optimizing TPS 3R composter and independent waste processing can reduce waste generation by 48%. Waste generation can be reduced with environmentally friendly and sustainable waste management. Recommendations to reduce waste generation are (1) adding TPS 3R units by maximizing composter processing so that the residue produced is reduced; (2) Independent waste management through low-waste houses needs to be socialized and campaigned, if needed issued as a mayoral regulation in household waste management; (3) Activation of waste banks that are no longer operating and improvement of waste bank management so that they can reach more people.